A randomized crossover study comparing different tacrolimus formulations to reduce intrapatient variability in tacrolimus exposure in kidney transplant recipients - Kim L. W. Bunthof (Clinical and Translational Science, 2022)
Abstract A high intrapatient variability (IPV) in tacrolimus exposure is a risk factor for poor long‐term outcomes after kidney transplantation. The main objective of this trial was to investigate whether tacrolimus IPV decreases after switching patients from immediate‐release (IR)‐tacrolimus to either extended‐release (ER)‐tacrolimus or LifeCyclePharma (LCP)‐tacrolimus. In this randomized, prospective, open‐label, cross‐over trial, adult kidney transplant recipients on a stable immunosuppressive regimen, including IR‐tacrolimus, were randomized for conversion to ER‐tacrolimus or LCP‐tacrolimus, and for the order in which IR‐tacrolimus and the once‐daily formulations were taken. Patients were followed 6 months for each formulation, with monthly tacrolimus predose concentration assessments to calculate the IPV. The IPV was defined as the coefficient of variation (%) of dose corrected predose concentrations. Ninety‐two patients were included for analysis of the primary outcome. No significant differences between the IPV of IR‐tacrolimus (16.6%) and the combined once‐daily formulations (18.3%) were observed (% difference +1.7%, 95% confidence interval [CI] −1.1% to ‒4.5%, p = 0.24). The IPV of LCP‐tacrolimus (20.1%) was not significantly different from the IPV of ER‐tacrolimus (16.5%, % difference +3.6%, 95% CI −0.1% to 7.3%, p = 0.06). In conclusion, the IPV did not decrease after switching from IR‐tacrolimus to either ER‐tacrolimus or LCP‐tacrolimus. These results provide no arguments to switch kidney transplant recipients from twice‐daily (IR) tacrolimus formulations to once‐daily (modified‐release) tacrolimus formulations when the aim is to lower the IPV.